Implementation of the Restorative Justice Concept with the Scope of the Police Handling Criminal Cases - Mundhi, Mundhi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this study is to determine and analyze the mechanism of the Police in using the concept of restorative justice in handling criminal cases. In this writing, the author uses a normative legal method with research specifications in the form of descriptive analysis. Within the framework of the Pancasila Legal State Concept, the restorative justice concept approach has only been implicitly recognized in the constitution and has only been partially regulated in several criminal law regulations, including the Child Criminal Justice System Law, the Special Autonomy Law for Papua Province, which has recognized the existence of a "consensus" method in enforcing criminal law, as well as institutional regulations such as the Police through the Circular of the Chief of Police Number SE / 8 / VII / 2018 concerning the Implementation of Restorative Justice. Criminal cases that can be handled with a restorative justice approach in the police if the investigation commencement order (SPDP) has not been submitted to the prosecutor's office. Not all cases can be resolved in that way, but they must also meet formal requirements, namely that there must still be an agreement between both parties and the fulfillment of the victim's rights and the perpetrator's responsibilities.